Hotel Corporate Social Responsibility and Residents Support for Tourism Development - Sorkhan, Vahid Babazadeh; Banejad, Babak; Ganji, Seyedeh Fatemeh Ghasempour (Journal of Tourism Management Research, 2020)
Nowadays, a hotel’s social responsibility has gained much attention in tourism literature. This research examines the impact of hotels’ social responsibility (HSR) perceived by residents’ on their community satisfaction and support of further tourism development (TD). Hotels’ social responsibility practices are measured as a multidimensional variable including economic, social and environmental dimensions using (Gursoy, Boğan, Dedeoğlu, & Çalışkan, 2019) questionnaire. The questions measuring support for TD and residents’ community satisfaction also extract from Gnji, Alikhani, Gholipour, Abcher, and Asri (2017) and Gursoy et al. (2019). The sample of 387 locals of Mashhad city, a famous tourist destination in Iran, was gathered. Questionnaires were examined by Structural Equation Modeling using Warp PLS 4 software. Findings show that perceived corporate social responsibility (CSR) practices increase residents’ community satisfaction and also their support for tourism development. Moreover, the effect of residents’ community satisfaction on their supportive behavior was significant. Lastly, the implication of this study for hotels and community planners are explained.